A simple high throughput assay to evaluate water consumption in the fruit fly. Issue 1 (December 2017) - Lau, Man-Tat; Lin, Yong; Kisling, Stefan; Cotterell, James; Wilson, Yana; Wang, Qiao-Ping; Khuong, Thang; Bakhshi, Noman; Cole, Tiffany; Oyston, Lisa; Cole, Adam; Neely, G.
Abstract Water intake is essential for survival and thus under strong regulation. Here, we describe a simple high throughput system to monitor water intake over time inDrosophila . The design of the assay involves dehydrating fly food and then adding water back separately so flies either eat or drink. Water consumption is then evaluated by weighing the water vessel and comparing this back to an evaporation control. Our system is high throughput, does not require animals to be artificially dehydrated, and is simple both in design and implementation. Initial characterisation of homeostatic water consumption shows high reproducibility between biological replicates in a variety of experimental conditions. Water consumption was dependent on ambient temperature and humidity and was equal between sexes when corrected for mass. By combining this system with theDrosophila genetics tools, we could confirm a role forppk28 andDopR1 in promoting water consumption, and through functional investigation of RNAseq data from dehydrated animals, we foundDopR1 expression in the mushroom body was sufficient to drive consumption and enhance water taste sensitivity. Together, we provide a simple high throughput water consumption assay that can be used to dissect the cellular and molecular machinery regulating water homeostasis inDrosophila .